Pengaruh Pengendalian Internal, Moralitas Individu Dan Efektivitas Terhadap Pengelolaan Keuangan Di Kecamatan Sukolilo Kota Surabaya - Adellya Tabitha Safa Marcella; Tituk Diah Widajantie (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this research is to examine and illustrate the ways in which internal control, personal morality, and efficiency have an impact on financial management in the Sukolilo District of Surabaya City. This study employs a quantitative methodology, which is typically a deductive method. Workers in the Sukolilo District of Surabaya City served as both the population and sample for this research. A total of 49 participants throughout 7 villages participated in the sample. Data utilized in this research are primary data, acquired by questionnaires sent to all employees in the Sukolilo subdistrict of Surabaya. Partial Least Squares is the data analysis method employed in this investigation (PLS). The study's findings indicate that neither internal control nor effectiveness has an impact on financial management. Individual morality affects financial management in Surabaya's Sukolilo district, however. Keywords: Internal Control, Personal Morality, Effectiveness, Financial Management